LAWEYAN DALAM PERIODE KRISIS EKONOMI HINGGA MENJADI KAWASAN WISATA SENTRA INDUSTRI BATIK TAHUN 1998-2004 - Majah, Ibnu (Journal of Indonesian History, 2014)
Laweyan is an unique, specific and historic area of ââindustrial centers of batik. In these developments, Laweyan has experienced the various dynamics of peoples lives. Laweyan entered a difficult period due to the economic crisis in 1997. After that, at the beginning of the Reformation era Laweyan condition gradually recovering. The results of the research showed that in post-crisis of economic in 1997 Laweyan conditions was undergone various changes. The economic conditions improved gradually returned, with the growth of new types of businesses in Laweyan. Laweyan society also become more open, after previously known as a closed society. In addition, Laweyan also began returning to preserve cultural traditions after almost gone. The conditions was more grow after the formation Laweyan as a tourist area in 2004. The establishment of that is start from the concerns of employers and community leaders in Laweyan against Laweyan potention. Then formed a forum with tasked to managing Laweyan as a tourism area. Post-declarations of Kampoeng Batik Laweyan on October 24th 2004, the forum also officially as Forum Pengembangan Kampoeng Batik Laweyan (FPKBL) or Kampoeng Batik Laweyan Development Forum. Â